PENGEMBANGAN METODE PEMBELAJARAN DEMONSTRASI PERSONAL DALAM MENUMBUHKAN MINAT WIRAUSAHA BAGI MAHASISWA PROGRAM STUDI TATA RIAS - Herina Yuwati; Tri Warsihapsari (Akademi Kesejahteraan Sosial AKK Yogyakarta, 2023)
This study aims to develop and analyze the application and feasibility of personal demonstration learning methods in fostering entrepreneurial interest for Cosmetology students. This research is a research and development R&D using ADDIE design (analysis, design, development, implementation, evaluation). The subject of this study is a student of AKS-AKK Yogyakarta Cosmetology study program. Data collection using questionnaires, observations, interviews and document studies. Analysis of research data using questionnaire validity and t-test. The results showed that: (1) The development of personal demonstration learning methods was carried out with development steps including; activities to create, modify teaching materials, and personal demonstration learning strategies; (2) The application of the personal demonstration method carried out in the bridal makeup practice course is very suitable because students can receive clear explanations of the material and follow every step of the demonstration easily; and (3) The feasibility of personal demonstration learning methods in fostering student entrepreneurial interest is declared feasible because of the results of different tests that show differences in student interest that has been given treatment